Rute Terpendek antar Asrama (Studi Kasus :Yayasan Mamba’ul Ma’arif Denanyar Jombang) - Cynthia Alvionita Ferima; Wiwit Denny Fitriana; Muwathoul Kamalia Aknaafi (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2023)
The data from the Mamba'ul Ma'arif Islamic Boarding School website page is that it houses 16 dormitories with male and female classifications. Some of the important factors include sowan, mineral water delivery, and garbage collection with several different access points. Therefore, of course, it is necessary to consider the shortest route, so that it can save time and minimize the distance to get to the dormitories. Graph theory, which is a branch of mathematics that can be implemented to find the shortest route. Researchers conducted research to determine the shortest route using the nearest neighbor method. The result of the shortest total distance from the implementation of the nearest neighbor method, the shortest route between the Mamba'ul Ma'arif Foundation dormitories Denanyar Jombang, is 1,920 meters. The aim of the results of this study can be used as a reference for the parties concerned to get the shortest route at the Mamba'ul Ma'arif Foundation, Denanyar Jombang.